Against demagogues : what Aristophanes can teach us about the perils of populism and the fate of democracy, new translations of the Acharnians and the Knights - Bartlett, Robert C., 1964-; Aristophanes; Aristophanes (Oakland, California : University of California Press, 2020)
"Against Demagogues presents Robert C. Bartlett's new translations of Aristophanes' most overtly political works, Acharnians and Knights. In these fantastically inventive, raucous, and raunchy comedies, the powerful politician Cleon proves to be democracy's greatest opponent. With unrivalled power, both plays make clear the dangers to which democracies are prone, especially the threats posed by external warfare, internal division, and class polarization. Combatting the seductive allure of demagogues and the damage they cause, Against Demagogues disentangles Aristophanes' serious teachings from his many jokes and pratfalls, substantiating for modern readers his famous claim to "teach justice" while "making a comedy" of the city. The book features an interpretive essay for each play, expertly guiding readers through the most important plot points, explaining the significance of various characters, and shedding light on the meaning of the plays' often madcap episodes. Along with a contextualizing introduction, the book offers extensive notes explaining the many political, literary, and religious references and allusions. Aristophanes' comedic skewering of the demagogue and his ruthless ambition-and of a community so ill-informed about the doings of its own government, so ready to believe in empty promises and idle flattery-cannot but resonate strongly with readers today around the world"--
Introductions: why we should read Aristophanes -- The Acharnians -- On the Acharnians -- The Knights -- On the Knights -- Appendix : Cleon's speech to the Athenian assembly (Thucydides, war of the Peloponnesians and Athenians 3.36-40).
Includes bibliographical references.
Description based on online resource; title from digital title page (viewed on September 24, 2020).
In English and Greek, Ancient.
eBooks on EBSCOhost
Keywords: Aristophanes -- Translations into English; Aristophanes -- Criticism and interpretation; Aristophanes; Democracy in literature; Populism in literature; Justice in literature; Populisme dans la littérature.; Justice dans la littérature.; POLITICAL SCIENCE / History & Theory; Democracy in literature; Justice in literature; Populism in literature; Ancient world guides; Aristophanes; athens; classics; comic; conservatism; danger; demagoguery; democracy; educational plays; external warfare; government; justice; liberalism; new translation; poetry; polarization; politics; power; threat; Electronic books; Criticism, interpretation, etc; Translations